Impact of the Global Financial Crisis on the Gulf Cooperation Council Countries and Challenges Ahead - Khamis, May (Departmental Papers; Departmental Paper ;, 2010)
This paper focuses on impact of the global financial crisis on the Gulf Cooperation Council (GCC) Countries and challenges ahead. The oil price boom led to large fiscal and external balance surpluses in the GCC countries. However, it also generated domestic imbalances that began to unravel with the onset of the global credit squeeze. As the global deleveraging process took hold, and oil prices and production fell, the GCC's external and fiscal surpluses declined markedly, stock and real estate markets plunged, credit default swap spreads on sovereign debt widened, and external funding for the financial and corporate sectors tightened. In order to offset the shocks brought on by the crisis, governments-buttressed by strong international reserve positions-maintained high levels of spending and introduced exceptional financial measures, including capital and liquidity injections. The immediate priority is to complete the clean-up of bank balance sheets and the restructuring of the nonbanking sector in some countries. Clear communication by the authorities would help implementation, ease investor uncertainty, and reduce speculation and market volatility.